SEBUAH PEMAHAMAN TENTANG SPIRITUALITAS PENDUDUK ASLI BATAK TOBA DAN PENGARUHNYA DALAM KEHIDUPAN SEHARI-HARI - Donobakti, Yohanes Anjar (LOGOS, 2019)
Spirituality is the dynamic motion of total life driven by the Holy Spirit that flows from the depths of the heart of oneself, lead him/her to the true actions and bring to the meaning ofÂ  life. This definition emerged and formed from the experiences oneself in every moment of his/her lives. Spirituality is always associated with every aspect of life in which he/she lives and works, in situations of joy and sorrow, with what and whom he/she interacts and communicates. Came to realize that the reality of the experience of life and the struggle to form a person's quality of life and character make him/her having a deep spirituality. Life will be more meaningful when people are aware and recognize that every event and experience the life through the intervention of God in everything around. We can feel the power of God (the Divine) presents and works in every word and action, in every step of the way of our life. Touched, awared and moved by God, the writer realizes that there is a process and a dynamic relation between human reality and divine reality in an indigenious people spirituality. As we have to know that the indigenious people have a spirituality. They see spirituality as a way of life in which all people are free to be themselves and practice life according to their norms. Therefore, this article is a reflection and understanding of the writer about spirituality of indigenious people, especially Batak Toba tribe in North Sumatera.